2021
DOI: 10.7759/cureus.19458
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Clinical Predictors of COVID-19 Severity and Outcomes

Abstract: Objective The present study aimed to assess the psychological and clinical determinants of coronavirus disease 2019 (COVID-19) and their association with the disease severity and outcomes. Methods This prospective study was conducted at Hayatabad Medical Complex, Peshawar-Pakistan. Admitted patients were screened for COVID-19 with reverse transcription-polymerase chain reaction (RT-PCR) and subsequently, 250 COVID positive patients were included in the final analysis. Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In many studies since the emergence of the COVID-19 virus, it has been concluded that individuals experience high levels of negative emotions such as fear, anxiety and anger [19].Participants noticed a wide range of mental break downs among the patients during the care ranging from fatigue, insomnia, anxiety, and stress. Severe anxiety and depression have been found among COVID-19 patients both previously and not previously diagnosed with psychological distress [20,21,22]. Difficulty breathing, prolonged quarantine, insufficient information, and social stigma were some causes of psychological distress [22].The holistic home care provided by the study participants to the COVID-19 patients included health assessment, nursing intervention, evaluation, reassessment, and practicing preventive measures.…”
Section: Limitationsmentioning
confidence: 99%
“…In many studies since the emergence of the COVID-19 virus, it has been concluded that individuals experience high levels of negative emotions such as fear, anxiety and anger [19].Participants noticed a wide range of mental break downs among the patients during the care ranging from fatigue, insomnia, anxiety, and stress. Severe anxiety and depression have been found among COVID-19 patients both previously and not previously diagnosed with psychological distress [20,21,22]. Difficulty breathing, prolonged quarantine, insufficient information, and social stigma were some causes of psychological distress [22].The holistic home care provided by the study participants to the COVID-19 patients included health assessment, nursing intervention, evaluation, reassessment, and practicing preventive measures.…”
Section: Limitationsmentioning
confidence: 99%
“…The increase in the consumption of white bread is accompanied by the need for complementary preparations, specifically jam. Jam is a semi-moist food that comes from the process of ripening fruit and sugar followed by or without the addition of acid, pectin, flavoring and coloring [1]. The results of several studies that have been carried out indicate that there are still problems, especially in terms of the shelf life of jams and the practicality of its use which is not optimal.…”
Section: Research Backgroundmentioning
confidence: 99%